Penataan Ruang dan Kenyamanan Sirkulasi Pengguna pada Minimarket (Studi Kasus: Alfamart Drive Thru Gading Serpong) - Prasetyo, Rizal Luhur; Maharani, Rizka Tiara (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
The development of the retail industry in Indonesia is experiencing rapid development, for example a large company in the retail sector which already has branch stores throughout Indonesia, namely PT. Sumber Alfaria Trijaya Tbk or what we often call Alfamart. Buyer comfort is the main focus in services at minimarkets, one of which is the convenience of circulation in minimarkets. This research exists because some visitors to minimarkets feel uncomfortable with the wide circulation provided by the store, especially in the area between the shelves of the products being sold. The method used is qualitative observation, where the data obtained is taken from the observation process which is presented in detail. The data analysis process will be supported by literature insights from books, journals and Alfamart Company data. The formulation of the problem from this research is that visitors feel that the space between the shelves for circulation is too narrow when picking up the product they want to buy. The purpose of this research is to determine the spatial arrangement at Alfamart Drive Thru Gading Serpong and whether the circulation of users in the store meets comfort standards for users inside.